Bioassessment using benthic macroinvertebrates of the water quality in the Tigreiro river, Jacuí Basin - doi: 10.4025/actascibiolsci.v35i4.18934 (Acta Scientiarum. Biological Sciences, 2013)
This study aimed to evaluate the water quality in the Tigreiro river, Jacuí river Basin, using different approaches. Benthic macroinvertebrates were sampled in July 2010 (winter) and February 2011 (summer) at five sites. In this study were analyzed: microbiological, physical and chemical variables, benthic macroinvertebrates richness and diversity, rapid ecological assessment protocol and benthic biotic indices (% EPT, BMWP’-IAP, ASPT, SOMI). A total of 5,852 individuals were collected belonging to 31 taxa of three Phyla: Annelida, Mollusca and Arthropoda. Chironomidae was the most abundant taxon (63.70%). A reduction in richness, diversity H’ and evenness J’ was observed from the initial stretches to the end stretches of Tigreiro river. The use of different approaches showed that sites in the rural area were less altered. The Tigreiro river was strongly impacted, mainly due to discharge of domestic effluents in the urban area, and the combination of different metrics was useful to detect impacted sites and the consequence for the water quality.